Studies in symbolic interaction. Vol. 30 - Denzin, Norman K. (JAI, 2008)
This book emphasizes critical approaches to the study of race, identity and self, as well as developments in interactionist theory, ethics and dramaturical studies.
Includes papers from "Peter M. Hall Lecture series."
Keywords: Symbolic interactionism.; Social interaction.; Interpersonal communication.; Social, group or collective psychology.; Psychology -- Social Psychology.; Language Arts & Disciplines -- Communication Studies.; Social Science -- Sociology -- General.; elektronické knihy; electronic books